Naming infinity : a true story of religious mysticism and mathematical creativity - Graham, Loren R.; Kantor, Jean-Michel. (Cambridge, Mass. : Belknap Press of Harvard University Press, 2009)
The intellectual drama will attract readers who are interested in mystical religion and the foundations of mathematics. The personal drama will attract readers who are interested in a human tragedy with characters who met their fates with exceptional courage--Freeman Dyson.
Storming a monastery -- A crisis in mathematics -- The French trio: Borel, Lebesgue, Baire -- The Russian trio: Egorov, Luzin, Florensky -- Russian mathematics and mysticism -- The legendary Lusitania -- Fates of the Russian trio -- Lusitania and after -- The human in mathematics, then and now.
Includes bibliographical references (pages 212-227) and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Mathematics -- Russia (Federation) -- Religious aspects; Mysticism -- Russia (Federation); Mathematics -- Russia (Federation) -- Philosophy; Mathematics -- France -- Religious aspects; Mathematics -- France -- Philosophy; Set theory; MATHEMATICS -- History & Philosophy; Mathematics -- Philosophy; Mysticism; Set theory; France; Russia (Federation); Mengenlehre; Rationalität; Mystizismus; Frankreich; Russland; SCIENCE / History; Electronic book; Electronic books